Automation of a garment sewing department assessment by smart simulation. (11th January 2023) - Cepolina, Francesco; Cepolina, Elvezia Maria
The textile-garment industry needs great production flexibility to adapt, in terms of sustainability, to the fickle fashion market. This study proposes a new simulation model of manufacturing and production processes, which can be used as design support, performance evaluation and plant management of highly flexible production systems such as those operating in the fashion sector. The proposed simulation model aims to support industries in increasing their reactive flexibility by adjusting the production set-up. It is a distributed discrete event simulator based on the easy re-composition of resources in the production layout and on the availability of intelligent process management and control modules. The simulator has been applied to optimise the production of children's garments. The development was done together with the production manager of an important European industry; the manager enjoyed the intuitive use of the software and the significance and reliability of the information obtained.